2017
DOI: 10.1080/09585192.2017.1322123
|View full text |Cite
|
Sign up to set email alerts
|

How a powerful audience and audience feedback moderate the relationship between performance-approach orientation and exaggerated self-promotion

Abstract: The drive for employees to perform well may tempt them to practice exaggerated self-promotion tactics. The supposition is that those with a strong performance-approach orientation are especially inclined to do this, but that contextual variables are relevant. In this study, I examined the influence of the combination of two contextual variables (perceived audience power and feedback) on the relationship between performance-approach orientation and exaggerated selfpromotion. A sample of 277 employees from two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…These results based on the newly developed scales for authentic and exaggerated self-enhancement may help resolve the mixed findings of self-promotion identified in previous studies given that existing scales conflate "valid claims of competence" with "exaggerating one's competence" or "lying" (cf. Molleman, 2019). Our new measures for authentic and exaggerated self-enhancement can also complement Yun, Takeuchi, and Liu (2007), who developed a new scale for self-enhancement motives (e.g., "I like to present myself to others as being a friendly and a polite person") but did not distinguish whether these motives are authentic or exaggerated.…”
Section: Implications For Theory and Practicementioning
confidence: 99%
See 3 more Smart Citations
“…These results based on the newly developed scales for authentic and exaggerated self-enhancement may help resolve the mixed findings of self-promotion identified in previous studies given that existing scales conflate "valid claims of competence" with "exaggerating one's competence" or "lying" (cf. Molleman, 2019). Our new measures for authentic and exaggerated self-enhancement can also complement Yun, Takeuchi, and Liu (2007), who developed a new scale for self-enhancement motives (e.g., "I like to present myself to others as being a friendly and a polite person") but did not distinguish whether these motives are authentic or exaggerated.…”
Section: Implications For Theory and Practicementioning
confidence: 99%
“…When targeting the latter, individuals may choose to self-enhance in a number of ways, including boasting, providing truthful biographical narratives, exaggerating successes, claiming credit, or humblebragging (Sezer et al, 2018). However, a clear theoretical or empirical distinction is lacking between promoting one's genuine or inauthentic attributes, with many assuming that self-promoters are at least embellishing their actual strengths (Molleman, 2019).…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the multiple contextual levels as our guiding classification (Miraglia & Johns, 2021), we found that 66% of these conditions were related to the individual level , which covers the characteristics of the feedback recipients. These span demographic characteristics such as age (Besen et al, 2013; Wang et al, 2015) and work experience (Dahling et al, 2012); and individual traits and states, including the Big Five (Guo et al, 2017), fixed versus growth mindset (Zingoni, 2017), self‐confidence (Bailey & Austin, 2006), self‐efficacy (Bailey & Austin, 2006), performance approach orientation (Molleman, 2019), learning goal orientation (Son & Kim, 2016), and feedback orientation (Gabriel et al, 2014).…”
Section: Resultsmentioning
confidence: 99%